TAX AND FISCAL AUDITAS THE REACTION OF PUBLIC AUTHORITIES ON TAX EVASION (Research Bulletins of the Faculty of Economic Sciences, 2021)
Tax evasion is aterm whch means illegaly avoiding paying taxes by people. This illegal practice is a seriosus problem of Polish Public Authorities. There can be plenty of tax evasion reasons, for instance: economic, social and legal. Tax evasion has got anegative influence to budget. It is very important that the public authorities should conduct effective audit activities.
Keywords: revenue control, tax audit, tax dodging